"Free Press Wins in Underhanded Fashion": Columnist Drew Pearson's Blackmail of General Douglas MacArthur. Issue 4 (2nd October 2022) - Feldstein, Mark
Abstract : Syndicated columnist Drew Pearson was one of the most important figures in the history of US investigative journalism, holding up its lonely banner in mid-twentieth-century Washington before its resurgence during the Vietnam War and Watergate scandals. His lacerating exposés of high-level political officials sent scoundrels to prison and made the crusading reporter the most feared and reviled journalist in the nation's capital from the early 1930s to the late 1960s. Yet a little-studied 1934 libel case against the muckraker by General Douglas MacArthur, settled out of court, nearly strangled Pearson's column in its infancy. Pearson's novel extralegal defense—blackmailing the general with secret love letters from his much younger Amerasian mistress—forced MacArthur to abandon his lawsuit, emboldened Pearson's aggressive reporting in the decades ahead, and prevented a potentially ruinous defeat in court that could have established a legal precedent that chilled press scrutiny of public officials. An analysis of previously unpublished archival materials—correspondence, diaries, memos, legal motions, and declassified FBI reports—reveals an intricate story of political and journalistic intrigue.